Assessment of Risk Factors Associated with Bone and Mineral Disease Post-Renal Transplantation: “The Experiences of Two Centers” - AL-Otaibi NE (Dove Medical Press, 2021)
Nouf E AL-Otaibi,1 Abdulmalik S Alotaibi,1 Nataleen A Albekairy,2 Mohammad S Shawaqfeh,3,4 Moawad Alotaibi,5 Shmeylan Alharbi,3,4,6 Abdulmalik Alkatheri,3,4,6 Abdulkreem M Albekairy3,4,6 1Clinical Pharmacy Department, College of Pharmacy, Umm Al Qura University, Makkah, Saudi Arabia; 2College of Medicine, King Saud bin Abdulaziz University for Health Sciences, Riyadh, Saudi Arabia; 3College of Pharmacy, Pharmacy Practice Department, King Saud bin Abdulaziz University for Health Sciences, Riyadh, Saudi Arabia; 4Department of Medical Research, King Abdullah International Medical Research Center (KAIMRC), Riyadh, Saudi Arabia; 5Family Medicine Department, Prince Sultan Military Medical City, Riyadh, Saudi Arabia; 6Pharmaceutical Care Services Department, King Abdulaziz Medical City, National Guard Health Affairs, Riyadh, Saudi ArabiaCorrespondence: Abdulkreem M AlbekairyCollege of Pharmacy, Pharmacy Practice Department, KSAU-HS, Riyadh, 11481, Saudi ArabiaTel +011-4295001; +966505550055Email bekairy@gmail.com; bekairya@ngha.med.saIntroduction: Bone and mineral disease risk following kidney transplantation becomes increasingly a health concern. The objective of this study is to evaluate the possible risk factors associated with bone and mineral disease post-renal transplantation.Methods: Retrospective observational study was carried out in two kidney transplant centers in Saudi Arabia, King Abdul-Aziz Medical City, Riyadh, and King Abdullah Medical City, Makkah. Patients who are 18 years or older were included. Patients with multiple organ transplantation and pediatric patients were excluded. Eligible kidney transplant patients were included. Baseline relevant laboratory values were recorded from the medical record from the admission and during the following 24 months post-transplantation. Chi-square tests were used to test for the presence of association between categorical variables. An independent t-test was also utilized to test for an association.Results: One hundred ninety-seven kidney transplant patients were included, bone mineral density testing and interpretation for patients before and after transplantation. About 23.4% had bone mineral density (BMD)tested prior to transplantation. Among those 2% had osteoporosis, 7.6% had osteopenia, and 13.7% had normal BMD. As for post-transplantation imaging, 26.9% had BMD tested. Among those 11.2% had osteoporosis, 10.7% had osteopenia, and 5.1% had normal BMD. The factors associated with post-transplantation osteoporosis were the history of osteoporosis, the number of rejections, the levels of total calcium, free calcium, and PTH. The factors associated with post-transplantation osteopenia were the history of osteoporosis, the history of osteopenia, the history of osteoarthritis, type of graft, using anti-coagulation, total calcium, free calcium, and phosphate levels. The factors associated with post-transplantation fracture were the history of osteopenia, type of graft, and total calcium levels.Conclusion: The factors associated with BMD were the history of osteoporosis, osteopenia, and osteoarthritis, number of rejections, levels of total calcium, free calcium, phosphate and PTH, type of graft, and anti-coagulation use.Keywords: osteoporosis, osteopenia, fracture, risk, kidney, transplantation